Pengaruh Keputusan Investasi, Kebijakan Hutang dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Sub-Sektor Kimia yang Terdaftar di Bursa Efek Indonesia (BEI) - Yunita Althin Natanael (ARBITRASE: Journal of Economics and Accounting, 2021)
This study aims to examine the effect of investment decisions, debt policy and profitability on firm value. The value of this company is measured by price to book value, using data from chemical sub-sector manufacturing companies listed on the Indonesian stock exchange. This study uses a quantitative approach. This study is 13 chemical sub-sector manufacturing companies listed on the Indonesian stock exchange with a sample of 11 companies. The sample was selected using a random sampling method, namely taking members of the sample and the population was carried out randomly without paying attention to the strata in the population. This study used secondary data in the form of annual financial reports. The analysis used in this study was multiple linear regeneration analysis to see if there were or Whether or not the influence of two or more independent variables on the dependent variable either jointly or individually. Before being tested with multiple linear regression, a classical assumption test is first performed.The results showed that together the independent variables of investment decisions, debt policy and profitability simultaneously have a significant effect on firm value and partially investment decisions have a significant effect on firm value while debt policy and profitability partially have no significant effect on firm value